The impact of loneliness on paranoia: An experimental approach. (March 2017) - Lamster, Fabian; Nittel, Clara; Rief, Winfried; Mehl, Stephanie; Lincoln, Tania
Abstract: Background and objectives: Loneliness is a common problem in patients with schizophrenia, and may be particularly linked with persecutory ideation. Nevertheless, its role as a potential risk factor in the formation and maintenance of persecutory delusions is largely unexplored. Methods: Loneliness was experimentally manipulated using a false-feedback paradigm in a non-clinical sample ( n  = 60). Change in state paranoia was compared between the induction of increased loneliness, the induction of reduced loneliness and a control condition. Distinct associations between pre-post scores of loneliness and state paranoia were examined at three (medium/high/low) levels of proneness to psychosis across the experimental conditions. Results: Reduction of loneliness was associated with a significant reduction of present paranoid beliefs, while induction of loneliness lead to more pronounced paranoia on trend significance level. Moreover, proneness to psychosis significantly moderated the impact of loneliness on paranoia. Persons with a pronounced level of proneness to psychosis showed a stronger reduction of paranoid beliefs as a consequence of a decrease in loneliness, than less prone individuals. Limitations: A limitation is the small size of our sample, which may have limited the power to detect significant within-group changes in state paranoia in the high-loneliness condition and changes in loneliness in the low-loneliness condition. Conclusions: The findings support the feasibility of the experimental design to manipulate loneliness and suggest that loneliness could be a cause of paranoia. However, the findings need to be confirmed in high risk samples to draw conclusions about the role of loneliness in the genesis of clinically relevant levels of paranoia and derive implications for cognitive behaviour therapy. Highlights: Reduction of loneliness leads to a decrease of paranoid beliefs. Induction of loneliness increases paranoid beliefs at trend level. Proneness to psychosis moderates the impact of loneliness on paranoia.